Optimizing the stacking sequence in dual-purpose body armors - Horsfall, Ian; Watson, Celia H.; Champion, Stephen M. (American Society of Mechanical Engineers (ASME), 2013)
Many police body armor systems are dual purpose, offering both ballistic and knife resistanceby combining a flexible ballistic textile pack with a stiffer knife resistant layer.The two types of protection differ in materials and mechanisms such that each individualcomponent may help or interfere with the function of the other. This paper investigatesthe effect on knife and ballistic penetration resistance when a single thin metal plate wasplaced at various different positions within an aramid textile armor pack. Two metalliclayers were used: aluminum 7075 and commercial purity titanium; these had similarareal densities and were positioned in the front, middle, and back of a 20 layer pack ofwoven KevlarVR 49. An instrumented drop weight machine was used to deliver a repeatableknife blade impact at comparable energy levels to those specified in the UK HomeOffice test standards for knife resistance. Ballistic tests were used to determine the V50ballistic limit velocity against typical 9mm and 0.357 Magnum handgun threats. Againsta stabbing threat, it was found that positioning the metal plate in the middle of the packprovided the greatest resistance to knife penetration by a factor of almost two, while aplate at the front of the pack provided less resistance and plates positioned at the rear ofthe pack provided the least resistance to penetration. Against the ballistic threat, the penetrationresistance of the textile pack can be significantly improved when a metal plate isat the front of the pack, while for all other positions the effect is negligible. However, thiseffect is sensitive to both the ammunition type and the metal plate composition. When themetal plate is positioned at the rear of the pack there is a significant decrease in theback-face deformation of the armor pack although, again, this effect is only present forcertain ammunition and metal combinations. The overall effect of combining soft andhard elements was that specific performance parameters could be substantially increasedby the correct combination. There were no significant negative effects, however, in anumber of cases, the combined systems performance was no greater than that of a singleelement type, despite the added weight.